Assessing Restoration along the Escalante River: Does Removal of an Invasive Tree Benefit the Arthropod Community? - Henden, Jacob; Ban-Herr, Allison; Aumann, Casey; Wellnitz, Todd A. (My University, 2016)
The Escalante River is the last remaining free-flowing river of its size in the western United States, and it faces environmental threats from the invasive Russian olive tree, Elaeagnus angustifolia (Reynolds and Cooper 2010). These trees outcompete native species and alter river ecosystems by creating heavy shade and channelizing rivers . In Grand Staircase Escalante National Monument, efforts are underway to restore the Escalante River corridor through long-term, large-scale removal of Russian olives. In collaboration with the Escalante River Watershed Partnership, we (the Biol-423, Collaborative Research in Biology class) assisted with Russian olive removal on the Escalante River and conducted research to assess the effects of removal on terrestrial and stream-dwelling arthropods. We hypothesized that arthropod richness and abundance would increase in areas where Russian olive was removed, and that these increases would be greater in areas that had more time to recover (Bateman et al. 2008).
Color poster with text, images, and graphs.
Keywords: Escalante River; Utah's Grand Staircase Escalante National Monument; E. angustifolia; Posters